MODEL PEMBELAJARAN LEARNING CYCLE (LC-5E) UNTUK MENINGKATAN HASIL BELAJAR KOGNITIF SISWA KELAS XI IPA SMA NEGERI 10 AMBON PADA KONSEP SISTEM PERNAPASAN MANUSIA - Flora Latuputty; H Tuaputty; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Learning Cycle Learning Model (LC-5E) is a flexible learning model and can improve the development of Concepts, namely how knowledge is constructed in the minds of students and students' skills in finding knowledge meaningfully. Method: This research is a descriptive research type. Population in this research is all student of class XI IPA SMA Negeri 10 Ambon which consist of 51 student and become sample of research in class XI IPA2 which amounted to 26 students. Data on biological learning results obtained through initial and final tests and observations to observe cognitive abilities were obtained through LKS results. Data analysis used qualitative descriptive analysis. Results: The results data obtained with the average score of achievement of the initial test 40 and are in the qualification failed, cognitive aspect 90 was in complete qualification. Based on the acquisition of the value of the evaluation results obtained that the learning by using the model of Learning Cycle LC-5e on Biology subjects can improve student learning outcomes of grade XI IPA2 SMA Negeri 10 Ambon. Conclusion: The improvement of learning by using Learning Cycle Learning Model (LC-5E), seen from the number of students who scored above KKM 75. Before doing the teaching and learning activities, the presentation of the number of students who scored KKM was 19%. After doing the teaching and learning activity that is the second meeting, the presentation of the number of students who get the value of KKM increased to reach the maximum number of 100%.